Identification of the Bok Interactome Using Proximity Labeling - Szczesniak, Laura M.; Bonzerato, Caden G.; Wojcikiewicz, Richard J. H. (Frontiers in Cell and Developmental Biology, 2021)
The function of the Bcl-2 family member Bok is currently enigmatic, with various disparate roles reported, including mediation of apoptosis, regulation of mitochondrial morphology, binding to inositol 1,4,5-trisphosphate receptors, and regulation of uridine metabolism. To better define the roles of Bok, we examined its interactome using TurboID-mediated proximity labeling in HeLa cells, in which Bok knock-out leads to mitochondrial fragmentation and Bok overexpression leads to apoptosis. Labeling with TurboID-Bok revealed that Bok was proximal to a wide array of proteins, particularly those involved in mitochondrial fission (e.g., Drp1), endoplasmic reticulum-plasma membrane junctions (e.g., Stim1), and surprisingly among the Bcl-2 family members, just Mcl-1. Comparison with TurboID-Mcl-1 and TurboID-Bak revealed that the three Bcl-2 family member interactomes were largely independent, but with some overlap that likely identifies key interactors. Interestingly, when overexpressed, Mcl-1 and Bok interact physically and functionally, in a manner that depends upon the transmembrane domain of Bok. Overall, this work shows that the Bok interactome is different from those of Mcl-1 and Bak, identifies novel proximities and potential interaction points for Bcl-2 family members, and suggests that Bok may regulate mitochondrial fission via Mcl-1 and Drp1.